Dendritic flux avalanches in superconducting films - Yurchenko, V.V.; Johansen, T.H.; Galperin, Y.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
Thermomagnetic instability in general, and dendritic flux avalanches in particular, have attracted considerableattention of both scientists and engineers working on superconductor applications. Though being harmful for the performance of many superconducting devices, the avalanches provide a fruitful playgroundfor experimental and theoretical studies of complex dynamics of the vortex matter. In this paper, we report on the progress in understanding the mechanisms responsible for the development of the giant magnetic avalanches. We review recent results on magneto-optical imaging of the fingering instability in superconducting films and analyze them basing on the recent theoretical model that establishes criteria for onset of the dendritic avalanches.